Triple Helix and academic entrepreneurial intention: Understanding motivating factors for academic spin-off among young researchers - Altaf Hussain Samo; Noor Ul Huda (Journal of Global Entrepreneurship Research, 2019)
Academic Spin-off is receiving a growing attention in entrepreneurship research due to increase in the number of ventures coming out from academia working at universities. The role of triple helix is key among many factors that derive young researchers to establish new venture as an outcome of their research. Thus, there is a need to determine the factors that derive young researchers for venture creation in order to identify and understand the determinants of Academic Entrepreneurial Intention (AEI) and how they are influenced by different helices of Triple Helix Model (THM). This study used sample of 310 young academic researchers studying/working in different universities of Pakistan. The finding of this study highlighted that government and academia have significantly positive relationship with the academic entrepreneurial intentions of young researchers while industry has positive, but insignificant relationship. The findings of this study have implication for promoting academic spin-off from developed and developing countries context.
Keywords: 650; Triple Helix model (THM); Spin-off; Theory of planned behavioral (TPB); Academic entrepreneurial intentions (AEI)